Precious Nickel Recovery from Palm Oil Mill Fuel Ash Waste (NiPOMFAW) Using Acidic Leaching Extraction (ALE) - Said, N.; Ahmad Shahroom, Mohd Shah; Malar V., Sivaguru; Syafiqah , A. Khairuddin; Hajar Athirah, M. Sukri; Aina A., Rahman (Trans Tech Publications, Switzerland, 2016)
This paper demonstrates precious recovery of nickel from physical pre-treated raw palm oil mill fuel ash waste (POMFAW). The acidic leaching extraction (ALE) using sulphuric and hydrochloric acids agents were carried out in a bath stirrer flask. Process parameter effects of acid concentration, solution pH and treatment time were investigated in the nickel recuperation. The highest nickel recovery (96.83%) was found by treatment time of 1 h, pH of 2.5 and hydrochloric acid concentration of 2.0 M. At the acids leaching higher than 2 M, the nickel recovery decreased. Results from acids leaching imply that nickel complex can be formed at substantial percentages within the acid concentration higher than 1 M. The hydrochloric acid provides impressive nickel compared sulphuric acid, and the POMFAW can be proposed as a substitute of non-renewable sources derived nickel for a promising material and the used ALE can be considered as a beneficial technique.